THE ANALYSIS OF THE POETRY “PAINTING THE MOTHER’S FACE” BY SEVRYADE ANUGRAH SAMBOLANGI FROM THE INNER STRUCTURE - Putri Juwita; Desniarti Desniarti; Fita Fatria (Sensei International Journal of Education and Linguistic, 2021)
Poetry is one of the most interesting and beautiful forms of literary work. The beauty of poetry does not only lies in words. The beauty of poetry is also formed by the physical and mental structures. The physical structure is the builder of poetry from the outside, while the inner structure of poetry is the spirit of a poem, so it is very important in a poem itself. This study aims to analyze the poem “Painting the Mother's Face” by Sevryade Anugrah Sambolangi from the Inner Structure. In this case, the observations or studies of poetry, especially in terms of language style are often carried out. The researcher chose Painting The Mother's Face poetry as the object of the study of poetry. The choice of poetry Painting The Mother's Face is based on the inner structure of the author which is interesting to study further. Those poetry contain the complexities associated with the language to be conveyed by the author. The researcher feel that the aspect of language has not been examined. These reasons encourage the researcher to conduct research on the language used by the author in conveying the meaning and message of the story to examine the inner elements, namely Themes, Tones and Feelings , Atmosphere , and Message.